Association between inflammatory bowel disease and risk of stroke: a systematic review and meta-analysis of cohort studies - Fan, Jin-Shan; Wang, Meng; Chen, Ni; Sun, Bai-chao; Zhang, Qi-Bing; Li, Yong; Huang, Ming-Jie (Frontiers in Neurology, 2023)
Background/objectives: Recently, four meta-analyses have explored the association between inflammatory bowel disease(IBD)and the risk of stroke. These researches have demonstrated that people with IBD may be at an increased risk of stroke. However, some limitations such as high heterogeneity, the lack of uniformity in the types of research ,especially the reuse of some sample sizes ,cannot be neglected. These factors reduce the credibility of their research conclusions. Therefore, we conducted a meta-analysis to explore this possible association.Methods: PubMed, Embase and Web of Science were search from inception to June 30, 2023. The random effects model with the generic inverse variance method was used in this meta-analysis. The Review Manager software was used to obtain all relative risks (RRs) and their 95% confidence intervals (CIs). Publication bias was tested, sensitivity and subgroup analyses were conducted to explore possible heterogeneities.